Sosialisasi Etika Penggunaan Sosial Media Dan Keamanan Penyebaran Informasi Di Pondok Pesantren Tahfidzul Qur’an Amanatul Huda, Kel.Tajur, Ciledug, Tangerang - Wasis Haryono; Tita Puspitasari; Asep Erlan Maulana (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Currently, the Tahfizhul Qur'an Amanatul Huda Islamic boarding school still carries out traditional da'wah, so that the da'wah that is carried out does not have a broad impact on society. Good preaching materials are only delivered to a handful of congregations. In carrying out da'wah, the Tahfizhul Qur'an Amanatul Huda Islamic Boarding School faces several challenges, one of which is technological challenges. In line with the very rapid advances in information and communication technology, social media has become a very influential tool in expanding the reach of preaching and religious education. In order to support this effort, there needs to be an effective socialization program. With this community service activity with the theme Socialization of the Ethics of Using Social Media and Security of Information Dissemination at the Tahfidzul Qur'an Amanatul Huda Islamic Boarding School, we will be able to carry out da'wah by utilizing social media by producing da'wah content that is right on target and can reach the community even wider.